Charge screening wormlike micelles affects extensional relaxation time and noodle formation. Issue 74 (30th August 2022) - Huang, Rui; McDowall, Daniel; Ng, Henry; Thomson, Lisa; Al-Hilaly, Youssra K.; Doutch, James; Burholt, Sam; Serpell, Louise C.; Poole, Robert J.; Adams, Dave J.
Abstract : The mechanical properties of gel noodles are controlled by screening of charges in the precursor micellar aggregates. Abstract : A functionalised dipeptide that self-assembles to form wormlike micelles at high pH can be treated as a surfactant. By varying salt concentration, the self-assembled structures and interactions between them change, resulting in solutions with very different shear and extensional viscosity. From these, gel noodles with different mechanical properties can be prepared.